Quality management system and sustainability: a Malaysian perspective - Khalili, Amjad; Ismail, Md Yusof; Karim, A.N. Mustafizul; , (Inderscience Enterprises Ltd., 2018)
Recently numerous studies have examined the interrelationships among quality management system (QMS) and sustainable performance (SP) of organisations, but none of the approaches addressed the issues in a holistic manner. Moreover, there is a very little empirical evidence concerning sustainability initiatives and how the QMS affects SP. This paper aims at investigating the linkage among QMS and SP of manufacturing sector of Malaysia applying techniques from SPSS and structural equation modelling (SEM). The developed model is examined in 329 industries in two phases. The first phase includes semi-structured interviews with Malaysian managers to examine the model's applicability. While in the second phase structured questionnaire is designed for gathering quantitative data. From the interviews with 12 managers, it implies that practices by local manufacturers are consistent with the developed model. Subsequently, the PCA and CFA were conducted to validate the hypothesis which reveals that SP is not affected by QMS.